Design and Study of Amorphous Wire Detection System - Pan, Feng (fi=Turun yliopisto|en=University of Turku|, 2018)
Anti-counterfeit technology is an important means for enterprises to protect their own intellectual property rights and economic interests. The existing of a magnetic material can be used in anti-counterfeit technology. If a glass-coated amorphous wire, made of cobalt-nickel-iron alloy, is placed in a magnetic field, it will disturb the magnetic field around it. Conventionally, the existence of amorphous wire can be detected using a scanning coil to generate a magnetic field, and a pair of differential coils to get a signal. Here a new detection method of a glass-coated amorphous wire is proposed based on a single pick-up coil. Because the magnetic field disturbance is weak, a series of hardware circuits were designed and implemented. The design scheme of hardware modules is introduced in details. After filtering the signal in hardware and software a little spike signal is extracted. The detection of the wire is based on the amplitude and duration of the spike signal. A signal processing algorithm was developed to ensure the detection. The algorithm was realized on the software implementation of a processor. In tests, the vertical detection distance of the glass-coated amorphous wire was 2 mm, the horizontal detection area 22 mm x 10 mm, and the minimum wire length 7 mm.